Youth Digital Technology Attitudes - Maon, Siti Noorsuriani; Ali, Syukrina Alini Mat; Azizam, Nor Azmaniza; Omar, Emi Normalina (Advances in Social Sciences Research Journal, 2023)
Today’s digital technologies have become essential tools in daily living. The young generation nowadays is very savvy in using digital technologies. It is essential to instill digital citizenship skills in preparing those who are also technology users for a digital society today. However, not all of them have undergone formal training to survive in a challenging environment in a digital world. Thus, this study aims to examine students’ attitudes and digital behaviour, particularly in rural schools, including how youth self-evaluate their perceptions of digital technologies, digital competencies, and attitudes towards digital technologies. Data were collected using survey questionnaires, with 210 valid responses. The study results revealed a statistically significant association between attitude toward digital use and digital competence dimensions, including technological, communication, and cognitive. Accessibility dimension in cyber-ethics was also statistically significantly associated with attitudes toward digital use among male students. To summarize, specific concerns and emphasis on youth digital technology usage and education must ensure that they are not left behind and vulnerable to cybercrime while fostering a responsible e-society with excellent digital citizenship characteristics.